Exploring English Literacy and Communication Needs among New Cadets in Maritime Education - Simanjuntak, Marudut Bernadtua; Sijabat, Panderaja Soritua; Barasa, Larsen; Malau, April Gunawan; Mudakir, Mudakir (Universitas Pahlawan Tuanku Tambusai, 2024)
This study delves into the intricate landscape of English literacy and communication needs among first-semester cadets at the Maritime Institute in Jakarta. Utilizing a qualitative descriptive approach in conjunction with document analysis, phenomenological observation, and strategic filling distribution, the research uncovers compelling insights into the challenges and aspirations within maritime education. Document analysis indicates a distinct emphasis on technical proficiency in Maritime English, yet a noticeable gap exists in addressing socio-pragmatic aspects of communication. Phenomenological observation reveals a spectrum of cadet engagement levels, prompting a critical re-evaluation of pedagogical strategies. Strategic filling distribution brings to light a disparity between perceived theoretical relevance and the practical application of English, advocating for a more scenario-based approach to language learning. The implications underscore the necessity for a paradigm shift in curriculum development and pedagogical practices. Recommendations propose curricular enhancement, pedagogical innovation, and industry collaboration to align educational objectives with the dynamic demands of the maritime sector. In conclusion, this research functions as a catalyst for transformative change in maritime language education, urging stakeholders to navigate towards a more comprehensive, industry-oriented approach that equips cadets with the nuanced proficiency demanded by real-world maritime scenarios